Peran Pusat Perbeniban Sebagai Mediator Stakeholders - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
ABSTRACT A seed program was formed and implemented in a country or region to serve good farmers for getting the certified seeds in a reasonable price. The final goal of the program was the increase of crop production through the use od the good quality of seeds. In fact, it was not easy to synchronize the sub-programs, those are actually dependent each others. The difficulties were due to the lacks of appropriate communicztions, and the whole management in the program including the availability of the seed sourses, human resourses. The stakeholders, the seed produsers, the traders, the mediators and the farmers are facing serious difficulties every time, to sell, to distribute, to get the seed due to the lacks of adequate informations. The Seed Centre, is formed to overcome those problems and to help the stake holders, for getting the informations, transcactions, trainning and consultayions, and other problems in terms of seeds and agribisnis. The centre plays the role to improve farmers adopting the certified seeds, and motivate them in doing agribisnis.